Razvoj predmeta telesna (športna) vzgoja in zdravje na Kitajskem - Kondrič, Miran (Šport (Ljubljana), 2024)
Physical education (PE) has passed different stages of development in the Chinese school curriculum, which was influenced by historical traditions, political and professional decision-makers, and curriculum assemblers. From a historical perspective, the subject was formed through a distinct imitation of foreign school systems to the integration of their patterns into the design of their system. After the creation of the People‘s Republic of China (1949), in PE, in comparison with previous models, transformations in the awareness of the meaning of the subject, contexts of implementation and legal formalities were visible. The main purpose of subject was focused on the effects of exercise on the body and physical practice and on integrating sports activities and competitions conducted after school into the school curriculum. Objectives were defined in the psychomotor, cognitive and social fields, and different teaching styles helped to achieve adequate outcomes in these three learning areas. Among the many changes that took place in Chinese society in the early years of the 21st century were the creation and implementation of a new national curriculum, which includes PE as one of the main subject areas. Unlike the previous PE curriculum, with goals focused on sports performance, the new one emphasizes the importance of health and fitness, which is reflected in the name changed from PE to PE and health“.
Keywords: China; curriculum; Kitajska; kurikulum; performance characteristics; physical education; sport; šport; športna vzgoja; značilnosti izvedbe